Pro-Kontra Terjemah Tafsiriyah Al-Qur’an Bacaan Mulia Karya H.B. Jassin - Habib Arpaja (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
This study aims to describe the discourse on the controversial translation of the Koran Bacaan Mulia by H.B Jassin. To achieve this goal, this study uses a qualitative method with analysis using content analysis. The results of this study that the translation of the Koran H.B. Jassin is unique because it displays the aesthetics of the Qur'an which is manifested in the form of a poetic translation. This work caused a stir in the country and invited the controversy of Muslims in Indonesia. Various accusations and criticisms were directed at H.B Jassin who was considered incompatible in the field of the Qur'an because he did not master Arabic and other sciences that supported the process of translating the Qur'an. The debate about whether the Qur'an tends to be poetic or prose, long before H.B Jassin's work related to the poetry of the Qur'an appeared. The majority of scholars are of the opinion that the Qur'an without being poetic already contains elements of very great poetry. Regarding the rhyme contained in the Qur'an, not only Muslim scholars have studied it. The orientalists also discussed it, such as Richard Bell, who argued that there are hidden rhymes. Differences in understanding the verses in the Koran itself have sometimes led to pros and cons, plus there have been translations in poetic form whose content sometimes does not match the original text. Apart from that, the translation of the Qur'an H.B Jassin; The Noble Readings of the Qur'an should be appreciated because it has colored the treasures of Islamic scholarship in Indonesia as well as a form of creativity in receptive to the Qur'an.